Nurses’ experiences of a screening and associated psychosomatic consultation service for mental comorbidities in somatic care inpatients – a qualitative study - Braunschneider, Lea-Elena; Seiderer, Johannes; Loeper, Siobhan; Löwe, Bernd; Kohlmann, Sebastian (Frontiers in Psychiatry, 2023)
Background: Screening for mental comorbidities and related liaison service reduce hospital length of stay in somatic hospital care. To develop, test and sustain such health care services, stakeholder feedback is required. One of the most important stakeholders in general hospital care and health care processes are nurses. Aim: The aim of this study is to explore nurses' experiencess on standardized nurse-led screening for mental comorbidities and associated psychosomatic consultation service in routine somatic inpatient care. Method: Semi-structured qualitative interviews with eighteen nurses involved in nurse-led screening service for mental comorbidities working on internal medicine or dermatological wards. Data were analyzed using thematic analysis. Results: Eight thematic groups were developed. On the one hand, participants reported benefits of screening: mental health education, general mental health awareness, holistic treatment approach, opportunity to build rapport with patients and reduction in workload. On the other hand, possible psychological effects of the intervention, reasons why patients may not want to be referred and application requirements to facilitate delivery were identified. None of the nurses opposed screening and related psychosomatic counseling for mental comorbidities in somatic care inpatients. Conclusion: All nurses endorsed the screening intervention and considered it meaningful. Nurses particularly emphasized the potential for holistic patient care and nurses’ improved skills and competencies, but partly critizised current application requirements. Relevance to Clinical Practice: This study adds on existent evidence on nurse-led screening for mental comorbidities and associated psychosomatic consultation service by emphasizing its potential to improve both patient care as well as nurses’ perceived self-efficacy and job satisfaction. To take full advantage of this potential, however, usability improvements, regular supervision, and ongoing training for nurses need to be considered.